2011 IEEE Congress of Evolutionary Computation (CEC) 2011
DOI: 10.1109/cec.2011.5949805
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary computation methods for helicopter loads estimation

Abstract: Abstract-The accurate estimation of component loads in a helicopter is an important goal for life cycle management and life extension efforts. This paper explores the use of evolutionary computational methods to help estimate some of these helicopter dynamic loads. Thirty standard time-dependent flight state and control system parameters were used to construct a set of 180 input variables to estimate the main rotor blade normal bending during forward level flight at full speed. Evolutionary computation methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…However in testing, this difference was much smaller and overall the performance was similar for the PSO, DE, and DO techniques. There was some underprediction for all methods in the three flight conditions, particularly for the k-leaders training scheme, but the frequency and degree of underprediction was much reduced as compared to previous results [1].…”
Section: A Full Mask Vs Reduced Mask Resultsmentioning
confidence: 44%
See 2 more Smart Citations
“…However in testing, this difference was much smaller and overall the performance was similar for the PSO, DE, and DO techniques. There was some underprediction for all methods in the three flight conditions, particularly for the k-leaders training scheme, but the frequency and degree of underprediction was much reduced as compared to previous results [1].…”
Section: A Full Mask Vs Reduced Mask Resultsmentioning
confidence: 44%
“…The most promising subsets were then selected and used as a base for model search. The data exploration followed in this work is described in detail in [1].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This analysis found that 5 time lags were necessary and therefore the predictor set consisted of the 30 FSCS parameters and their 5 time lags for a total of 180 predictors [1], [2]. The Gamma test then steered the evolutionary process used for data exploration.…”
Section: Methodsmentioning
confidence: 99%
“…Preliminary work exploring the use of various computational intelligence techniques to assist in estimating helicopter loads showed that reasonably accurate and correlated predictions for the main rotor normal bending could be obtained for the flight condition forward level flight at full speed using only a reduced set of flight state and control system parameters [1], [2]. However, the main weakness of these previous efforts has been the tendency to underpredict the target signal.…”
Section: Introductionmentioning
confidence: 99%